Media Representations of Police and Crime - Colbran, M. author. aut Link
XI, 253 p.
Keywords: This unique book explores the social processes which shape fictional representations of police and crime in television dramas. Exploring ten leading British and European police dramas from the last twenty-five years, Colbran, a former scriptwriter, presents a revealing insight into police dramas, informed by media and criminological theory.